Factors affecting whole grain consumption: primary focus health factors - Scott, Willie Henry Jr. (Kansas State University, 2008)
We designed a mail survey to investigate consumer choices between whole-grain and regular grain products. Consumption of whole-grain foods has been linked to numerous health benefits including reduced risk of heart disease, diabetes and obesity. The prevalence of obesity has increased in recent decades and has been shown to be negatively correlated with education levels and income. Data from the survey are used to investigate correlations between the likelihood of choosing whole-grain alternatives and various demographic and behavioral characteristics including an individual's Body Mass Index (BMI). We also investigate the impact on consumer choices of providing information about the health benefits of whole-grain foods. Results indicate that education level and the use of food labels are both positively correlated with the likelihood of choosing whole-grain foods. Provision of information about health benefits also had a positive impact on the likelihood of choosing a whole-grain over a conventional grain product, but given a low sample size in this study the effect was not statistically significant. Choices were found to be largely insensitive to changes in relative prices, and no correlation was found between BMI and the likelihood of choosing a whole-grain product.
Keywords: Consumer Attitudes Whole-grains Logit; Economics, Agricultural (0503)